THE LIMITS OF PROSECUTOR'S SUPERVISION OF THE OBSERVANCE OF CITIZEN'S RIGHTS AND FREEDOMS: THEORETICAL AND LEGAL ANALYSIS - Sobitova Umidakhon Murod qizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This scientific article examines the theoretical and practical aspects related to determining the boundaries of prosecutorial supervision in the field of ensuring the rights and freedoms of citizens. Special attention is paid to the criteria that limit the prosecutor's interference in the activities of state authorities, organizations, and officials. The article emphasizes the importance of maintaining a balance between effectively protecting the interests of individuals and preventing an excessive expansion of the prosecutor's supervisory powers. The article concludes that it is necessary to improve the regulatory framework and the practice of prosecutorial supervision as an important condition for strengthening the guarantees of citizens' rights and freedoms.